STOREKEEPER RELATED1/G-Element Binding Protein (STKR1) Interacts with Protein Kinase SnRK1. Issue 2 (30th November 2017) - Nietzsche, Madlen; Guerra, Tiziana; Alseekh, Saleh; Wiermer, Marcel; Sonnewald, Sophia; Fernie, Alisdair R.; Börnke, Frederik
Abstract : STKR1-overexpressing plants show many phenotypic changes that have previously been associated with SnRK1 overexpression, and thus STKR1 could act as a downstream component of SnRK1 signaling. Abstract: Sucrose nonfermenting related kinase1 (SnRK1) is a conserved energy sensor kinase that regulates cellular adaptation to energy deficit in plants. Activation of SnRK1 leads to the down-regulation of ATP-consuming biosynthetic processes and the stimulation of energy-generating catabolic reactions by transcriptional reprogramming and posttranslational modifications. Although considerable progress has been made during the last years in understanding the SnRK1 signaling pathway, many of its components remain unidentified. Here, we show that the catalytic α-subunits KIN10 and KIN11 of the Arabidopsis ( Arabidopsis thaliana ) SnRK1 complex interact with the STOREKEEPER RELATED1/G-Element Binding Protein (STKR1) inside the plant cell nucleus. Overexpression of STKR1 in transgenic Arabidopsis plants led to reduced growth, a delay in flowering, and strongly attenuated senescence. Metabolite profiling revealed that the transgenic lines exhausted their carbohydrates during the dark period to a greater extent than the wild type and accumulated a range of amino acids. At the global transcriptome level, genes affected by STKR1 overexpression were broadly associated with systemic acquired resistance, and transgenic plants showed enhanced resistance toward a virulent strain of the biotrophic oomycete pathogen Hyaloperonospora arabidopsidis Noco2. We discuss a possible connection of STKR1 function, SnRK1 signaling, and plant immunity.